(untitled) (Research, Society and Development, 2022)
Antibiotics are fundamental in the treatment of infectious diseases, as they are drugs capable of inhibiting the growth or killing the bacteria responsible for the infection. However, its inappropriate use can cause irreparable damage to humanity, such as a significant advance in bacterial resistance, impairing the effectiveness of treatment and increasing mortality from infectious diseases. The aim of this study was to analyze scientific data about the consequences associated with the inappropriate use of antibiotics. A narrative literature review was carried out, in the SCIELO, LILACS and MEDLINE databases, on the topic. Antimicrobials are among the most commercialized drugs worldwide, in different classes to perform specific actions depending on the strain, site and severity of infection. The problem of bacterial resistance is associated with its indiscriminate and inappropriate use, giving rise to multi-resistant bacteria, which are no longer sensitive to any type of substance. The impact of this resistance is collective and global, representing a threat to the continuity of life on the planet, as well as configuring an important global public health problem. Therefore, it is essential to minimize the emergence of antibiotic-resistant bacteria, through more correct prescriptions and better guidance to users on the prudent use of antibiotic therapy.